The Influence of Leadership, Work Motivation, and Work Ethic on Employee Performance - Azuma, Muhammad Iqbal; Widodo, Zandra Dwanita; Al Husin, Syahri (Forum Kerjasama Pendidikan Tinggi, 2025)
Performance is the result of a person’s work or achievement of targets that must be achieved or tasks that must be carried out according to the responsibilities of each individual within a certain period of time. This study aims to analyze the effect of leadership, work motivation, and work ethic on the performance, both partially and simultaneously. This study uses primary data and is quantitative. The quality of data in this study was tested with validity and reliability testing. Data collection methods using observation and questionnaires. The research sample was 66 people selected using simple random sampling technique from a population of 194 people. Multiple linear regression analysis was used in this study. The results showed that leadership partially influenced employee performance by 16.4%. Work motivation has an impact of 22.4% and work ethic of 28.6. The three variables simultaneously have a significant influence on employee performance with a significant value of 0.000 less than 0.05. The 60.5% figure obtained from the coefficient of determination shows that variations in performance can be explained by leadership, work motivation, and work ethic, and the remaining 39,5% is infulenced by other variables not studied.